Neural correlates of conscious processing of emotional faces: Evidence from event-related potentials. (15th April 2023) - Sun, Bo; Zeng, Xianqing; Chen, Xiaomin; Zhao, Jin; Fu, Shimin
Abstract: There is a theoretical debate between the early and late neural correlates of consciousness (NCCs). Previous studies using neutral face stimuli supported an early NCC and suggested that visual awareness negativity (VAN) is associated with consciousness, while late positivity (LP) reflects post-perceptual activity. However, emotional faces may help to examine the relationship between LP and consciousness due to the differences in late processing between emotional and neutral faces. To explore the effects of facial emotional information on NCCs, the present study manipulated consciousness with the inattentional blindness paradigm and used happy, fearful, and neutral faces as visual stimuli. The results showed that the conscious processing of emotional faces was correlated with VAN and LP, while the conscious processing of neutral faces was associated with VAN. First, the results suggest that VAN is an NCC, and the relationship between LP and consciousness is affected by facial emotional information. Second, VAN reflects the early perceptual experience of emotional faces, whereas LP may reflect the late conscious processing of emotional faces. Furthermore, source localization analysis showed that the LPs of emotional faces were mainly located in the frontal and parietal lobes, whereas those of neutral faces showed no significant activation. This suggests that facial emotional information may affect the brain regions associated with conscious processing. Time–frequency analysis showed that conscious processing is related to the enhancement of alpha and theta oscillation, indicating that conscious processing may be associated with the suppression of irrelevant stimuli. Overall, the present study suggests that the integration of the theories that support early and late NCCs helps explain the conscious processing of emotional faces.